Ethical conflicts in a public management context: conscientious objection and abortion in the Spanish public health network - Vilas-Iglesias, María Soledad; Caamaño-Alegre, José (Acta Bioethica, 2024)
This article argues, first, that (1) the persistence at the international level of ethical debates on the moral status of nasciturus and (2) the traditional ethical commitment of health professionals to the health of both the pregnant woman and the unborn child, give full sense and validity to the right to conscientious objection of these professionals. However, where legal abortion is configured as a health care service, the difficulty of managing this service and, at the same time, the moral conflict expressed by conscientious objection arises. If, in a public health institution, objection is widespread, there is a dilemma with ethical implications between referring pregnant women to other institutions or implementing staff integration strategies at the health service level. In the case of Spain, a reform of the Organic Law on Sexual and Reproductive Health and the Voluntary Interruption of Pregnancy (LOSSRIVE) was approved this year, which shows a more stringent willingness that conscientious objection does not prevent access to abortion in public health institutions, establishing specific provisions to that effect. Based on the parliamentary work, we identified the main points of political discrepancy, which remit to different basic positions on abortion and affect the very approach of the reform, as well as other not always new elements —some of them were already in the LOSSRIVE or were already being applied at the regional level with the approval of the Constitutional Court.